LO80: Chest radiograph ordering for acute asthma presentations to emergency departments in Alberta: regional, site, and physician level variation. (15th May 2017) - Krebs, L.; Alexiu, C.; Villa-Roel, C.; Holroyd, B.R.; Ospina, M.; Pryce, C.; Bakal, J.; Jelinski, S.E.; Rowe, B.H.
Abstract : Introduction: Most acute asthma presentations to the emergency department (ED) are uncomplicated and do not require chest radiographs (CXR). Evidence suggests that the proportion of acute asthma patients receiving CXRs in the ED is high and varies substantially within and across sites and studies. This study explored CXR ordering and variation in acute asthma presentations to Alberta's EDs.Methods: Administrative health data for Alberta was obtained from the National Ambulatory Care Reporting System (NACRS) for all adult (>17 years) acute asthma (ICD-10-CA: J45) ED visits from 2011-2015. Patients with a primary or secondary diagnosis of asthma were included, provided they had a Canadian Triage and Acuity Scale score of 2-5. NACRS data were linked with Alberta Health Services' (AHS) diagnostic imaging database. Preliminary analysis on variation in imaging at the zone, ED site, and physician level was completed using SAS (v.9.4). Physicians who saw less than an average of 10 asthma patients per year were excluded.Results: Overall, 51, 511 acute asthma ED presentations occurred ( 10, 000/year). The average proportion of CXRs among presentations was 39.5% (2011-2015) with an average annual increase of 6.7%. From 2011-2015, CXR ordering varied across the five AHS zones (variation [V]: 25%; range: 26.0%-51.0%). Substantial variation was observed across ED sites V: 60%; range: 5.9-66.4%) and physicians (V: 89%; range: 1.4-90.6%). The mean CXR ordering among physicians was 44%.Conclusion: From 2011-2015, CXR use among acute asthma ED presentations has increased. Substantial variation in CXR use suggests that evidence-based interventions are needed to improve imaging appropriateness.